The reciprocal longitudinal relationship between body mass index and subjective well-being in China. (March 2022) - Fang, Junyan; Wen, Zhonglin; Ouyang, Jinying; Huang, Guomin; Liu, Xiqin
Abstract: The relationship between body mass index (BMI) and subjective well-being (SWB) has been widely discussed in empirical literature. However, most previous studies were cross-sectional and inadequate to assess directionality. The current study examines the prospective relationship between BMI and SWB by analyzing nationally representative longitudinal data from 2009 to 2015. Eligible subjects were those who participated in a three-wave measurement ( n  = 18, 443, age 13–99 years). We used a random-intercept cross-lagged panel model (RI-CLPM) to investigate the dynamic relationship between BMI and SWB, controlling for covariate effects. Results indicated that BMI and SWB were positively associated at the population level, and there was a reciprocal relationship at the individual level. An individual's BMI levels positively influenced his or her subsequent SWB values, with effects ranging from 0.15 (95% CI: 0.09–0.22) to 0.16 (95% CI: 0.09–0.24). At the same time, an individual's SWB levels positively influenced subsequent BMI values, with effects ranging from 0.12 (95% CI: 0.08–0.17) to 0.17 (95% CI: 0.10–0.24). This mutual reinforcement process supports the "jolly fat" hypothesis from a longitudinal perspective, implying that the psychosocial burden of excess weight may not hold in China. The implications are that mental health interventions could help prevent the risk of being underweight, and nutritional care would contribute to the creation of a happier society. Highlights: BMI and SWB are positively associated at the population level. One's BMI levels positively influence subsequent SWB values, and vice versa. The mutual process implies psychosocial burden of obesity may not hold in China.